DOES POST MENOPAUSAL BLEEDING ALMOST ALWAYS POINT TOWARDS A SINISTER CAUSE: CLINICAL SCENARIO IN THE “CANCER BELT OF NORTH INDIA” – A PROSPECTIVE HOSPITAL-BASED STUDY. - Ganjoo, Dr.Sandesh; Grover, DR.Seema; kaul, Dr. Varun; Kaur, Dr. Harpreet; Nibhoria, Dr. Sarita; Mattu, Dr. Sheena (Student’s Journal of Health Research Africa, 2023)
Background: Bleeding after menopause can be an early sign of malignancy in the cervix and the inner layer of the uterus. Detecting the malignancy earlier can make such malignancy manageable. The aim of this study is to determine the occurrence of bleeding after menopause in North Indian women. Methods: This was a survey-based prospective study carried out over a span of two years (January 2017 to December 2018) in the Department of Obstetrics & Gynaecology at Guru Gobind Singh Medical College and Hospital, Faridkot, Punjab, a government hospital of tertiary care. The remaining 262 women were considered as the subjects for this study. Results: Abnormal mass was detected in the abdomen and the pelvic region of 21 women. When a speculum was inserted a mass was observed in the cervical region in 116 women, most of these masses were due to malignancy. Erosion in the cervix was observed in 42 women. A relatively small number of women had growth in their vagina and vulva region. 43.5 % of the women had heavy cervical mass, 2.3% of the women had abnormal growth in the myometrium of the uterus, 6.9% of women had malignancy in the inner layer of the uterus, 5.3% of the women had abnormal growth in the endometrium and 0.4% had cancer in the ovary. Endometrium was thicker than 10mm in 3.4% of the women. Conclusion: The bleeding after menopause is generally ignored as it seems harmless. However, it can indicate malignancy of the endometrial and cervical tissues. Recommendation: Diagnosis and evaluation of the cause can reduce the mortality and morbidity rates.